1989
DOI: 10.1139/z89-017
|View full text |Cite
|
Sign up to set email alerts
|

Body temperatures and movements of hibernating snakes (Crotalus and Thamnophis) and thermal gradients of natural hibernacula

Abstract: 1989. Body temperatures and movements of hibernating snakes (Crotalus and Thamnophis) and thermal gradients of natural hibernacula. Can. J. Zool. 67: [108][109][110][111][112][113][114]. Although temperate zone snakes spend a large part of each year in hibernation, we know relatively little about their behavior during this part of the annual cycle. We used radiotelemetry to monitor temperatures and movements of hibernating rattlesnakes (Crotalus viridis) in southern British Columbia and garter snakes (Thamnoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 9 publications
5
25
0
Order By: Relevance
“…Hawley and Aleksiuk, 1975;Hawley and Aleksiuk, 1976;Jacob and Painter, 1980;Crews and Garstka, 1982;Licht, 1984;Whittier et al, 1987a;Macartney et al, 1989;Grobman, 1990;Crawford, 1991). For example, Etheridge et al (Etheridge et al, 1983) demonstrated experimentally that increasing ambient temperatures stimulate emergence of the six-lined racerunner (Cnemidophorus sexlineatus) from winter dormancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hawley and Aleksiuk, 1975;Hawley and Aleksiuk, 1976;Jacob and Painter, 1980;Crews and Garstka, 1982;Licht, 1984;Whittier et al, 1987a;Macartney et al, 1989;Grobman, 1990;Crawford, 1991). For example, Etheridge et al (Etheridge et al, 1983) demonstrated experimentally that increasing ambient temperatures stimulate emergence of the six-lined racerunner (Cnemidophorus sexlineatus) from winter dormancy.…”
Section: Introductionmentioning
confidence: 99%
“…However, some species (especially those inhabiting extreme northern latitudes) can occupy underground dens at depths where ground temperatures do not change significantly before spring emergence. Red-sided garter snakes (Thamnophis sirtalis parietalis) in Manitoba, Canada emerge at body temperatures as low as 0.5°C (Lutterschmidt et al, 2006), suggesting that increases in ground temperatures may not be the only thermal cue utilized by ectotherms (Macartney et al, 1989;Lutterschmidt et al, 2006). Indeed, emergence of red-sided garter snakes from hibernation may be regulated, at least in part, by an endogenous circannual cycle (Lutterschmidt et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals from northern populations frequently migrate considerable distances between summer grounds and communal dens, where they hibernate in large numbers (Gregory 1982). Indeed, the availability of suitable den sites may be one factor that limits the distribution of garter snakes in northern regions (Gregory 1982;Macartney et al 1989). Presumably temperature, moisture content, and ventilation are criteria important in the choice of hibernation sites.…”
Section: Introductionmentioning
confidence: 99%
“…Our data suggest that snake populations that hibernate in the lower part of the thermal range of 0 Ce10 C (Macartney et al, 1989) should have less infection during the spring than snake populations that hibernate in the upper part of the thermal range of 0 Ce10 C. In addition, our data also suggest that with increasing global temperatures, snake populations will be more vulnerable to O. ophiodiicola infection in regions experiencing frequent mild winter conditions.…”
Section: Discussionmentioning
confidence: 53%